Complete genome sequence of Acetohalobium arabaticum type strain (Z-7288T). Issue 1 (July 2010) - Sikorski, Johannes; Lapidus, Alla; Chertkov, Olga; Lucas, Susan; Copeland, Alex; Glavina Del Rio, Tijana; Nolan, Matt; Tice, Hope; Cheng, Jan-Fang; Han, Cliff; Brambilla, Evelyne; Pitluck, Sam; et al.
Abstract Acetohalobium arabaticum Zhilina and Zavarzin 1990 is of special interest because of its physiology and its participation in the anaerobic C1 -trophic chain in hypersaline environments. This is the first completed genome sequence of the familyHalobacteroidaceae and only the second genome sequence in the orderHalanaerobiales . The 2, 469, 596 bp long genome with its 2, 353 protein-coding and 90 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.